2016
DOI: 10.4149/neo_2016_501
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma, immunotherapy and minimal residual disease

Abstract: Multiple myeloma (MM) is an incurable heterogeneous hematological malignancy in which relapse is characterized by re-growth of residual tumor and immune suppression with a complex biology that affects many aspects of the disease and its response to treatment. The bone marrow microenvironment, including immune cells, plays a central role in MM pathogenesis, survival, and drug resistance. The advances in basic and translational research, introduction of novel agents, particularly combination therapies, improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The study by Anderson et al[6] also showed that MRD plays an important role in determining the condition, evaluating prognosis and guiding subsequent therapy. However, because the MRD detection method is not standardized and the sensitivities of different instruments are different, it varies among different medical institutions[7,8]. Therefore, attention should be paid to identifying a highly sensitive and reliable indicator for the evaluation of prognosis using MRD detection technology.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Anderson et al[6] also showed that MRD plays an important role in determining the condition, evaluating prognosis and guiding subsequent therapy. However, because the MRD detection method is not standardized and the sensitivities of different instruments are different, it varies among different medical institutions[7,8]. Therefore, attention should be paid to identifying a highly sensitive and reliable indicator for the evaluation of prognosis using MRD detection technology.…”
Section: Introductionmentioning
confidence: 99%
“…Given the success of targeted immunotherapy with monoclonal antibodies in other cancers, recent research has focused on the development of this class of drugs for multiple myeloma [4][5].…”
mentioning
confidence: 99%
“…It is estimated that approximately 30,280 cases of myeloma are expected to be diagnosed in 2017 and almost 12,590 myeloma patients will die from the disease [2]. While autologous stem cell transplantation (ASCT) and high-dose chemotherapy have recently improved the overall survival of MM patients [3,4], the minimal or measurable residual disease (MRD) followed by ASCT and the inevitable drug resistance to chemotherapeutic drugs are still major causes of MM progression and relapse [5,6]. Therefore, cancer immunotherapy capable of killing multi-drug-resistant malignant cells and stabilizing or even clearing the MRD should be an effective strategy for patients with relapsed/ refractory MM [7,8].…”
mentioning
confidence: 99%